Risk factors for preeclampsia: A case-control study in Makassar City and Gowa Regency, Indonesia - Andi Sitti Rahma; Rini Fitriani; Sari Ifdiana Jalal; Syarifah Intan Nurfitri (AcTion: Aceh Nutrition Journal, 2026)
Preeclampsia remains a serious pregnancy complication with a high prevalence in Indonesia. This case-control study, conducted in Makassar City and Gowa Regency (August–December 2024), aimed to analyze the risk factors for preeclampsia in 78 pregnant women (>20 weeks gestation), diagnosed based on hypertension and proteinuria. Data on obstetric history, diet (FFQ), and anthropometrics were collected, including serum zinc levels measured using ELISA. Independent t-tests indicated a significantly higher pre-pregnancy Body Mass Index (BMI) in the preeclampsia group (p<0.05). A Chi-square test revealed that a history of preeclampsia served as an absolute predictor within this sample (95% CI: ∞). Multivariate Binary Logistic Regression showed that Weight Gain was the only statistically significant independent risk factor for preeclampsia incidence (p=0.045), with the risk category yielding an Odds Ratio (OR) of 2.928 (95% CI: 1.022–8.387). Other variables, including BMI, were not significant (p>0.05). Dietary patterns (fish intake) also showed an association with preeclampsia in preeclampsia women (p=0,022; OR 9.909 and 95% CI 1.396-70.348). The conclusion is that a history of preeclampsia is an absolute predictor in this study sample. There was a relationship between weight gain during pregnancy and fish intake with the incidence of preeclampsia in the study area.